CAUSES OF MORAL DECADENCE AND THEIR EFFECTS ON THE BEHAVIOUR OF ADOLESCENT STUDENTS IN SENIOR ^SECONDARY SCHOOLS IN ZAMFARA STATE - Mayanchi, M L (Sokoto Educational Review, 2011)
This study is titled "causes of moral decadence and its effects on the behaviour of adolescents students in senior secondary schools in Zamfara State” Three research hypotheses were formulated to establish the causes of moral decadence. Literature that bears relevance with this study were properly reviewed. The research design used was descriptive survey type. The population of this study was made up of adolescent students in senior secondary schools in Zamfara State, teachers and parents of the students. Random sampling technique was used to select the schools where respondents were drawn from. The sample consists of 379 respondents. The research instrument used was adopted from Idowu (2002). The instrument was administered and the results showed that there was no significant difference in the mean opinions of the respondent’s for all the hypotheses formulated through the use of t-Test for hypotheses 1 and 2, and ANOVA for hypotheses 3. The findings revealed that most of the respondents agreed that unfriendly home environment, the tack of concern by parents among other things form part of the causes of moral decadence among adolescents students o f senior secondaiy schools in sokoto Zamfara States. Based on these findings, it was recommended that parents should be good disciplinarians, the. government should supply adequate facilities to create room fo r effective teaching and learning process and students should b e . encouraged to join youth clubs/societies meant fo r character training.